2021
DOI: 10.1021/acs.inorgchem.1c00073
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Insights into the Electronic Properties of Anionic N-Heterocyclic Dicarbenes through the Rational Synthesis of Their Transition Metal Complexes

Abstract: The lithiation of the NHC ligand backbone in Cp(CO)2Mn(IMes) followed by transmetallation on the C4 carbenic position with Cp(CO)2FeI led to the heterobimetallic complex Cp(CO)2Mn(μ-dIMes)Fe(CO)2Cp bearing the anionic ditopic imidazol-2,4-diylidene dIMes ligand. Subsequent treatment of the later with TfOH induced a selective decoordination of the [Cp(CO)2Mn] fragment to form the cationic abnormal NHC complex [Cp(CO)2Fe(aIMes)](OTf), which was further derivatized into the bis(iron) dIMes complex [Cp(CO)2Fe(μ-dI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 100 publications
1
11
0
Order By: Relevance
“…The latter E int values and the above QTAIM descriptors of the Pd–CO bonds are in the same range as those calculated for Cu­(I)–CO bonds in zeolites . As suggested by the X-ray structure of Pd complex [ 4 ]­(OTf) ( vide supra ), a weak attractive nonbonding CC···CO interaction was confirmed by the presence of the bond critical point between the corresponding C ipso and carbonyl carbon atoms, and its energy was estimated to be about 1.7 kcal mol –1 . While such interligand bonding is more common for carbonyl-containing transition metal NHC complexes exhibiting (pseudo)­octahedral, tetrahedral, and trigonal-bipyramidal geometry, the examination of CCDC base revealed only two examples of square-planar Rh­(I) complexes based on chelating bidentate NHC ligands, which display similar structural features as observed in the complex [ 4 ]­(OTf) .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The latter E int values and the above QTAIM descriptors of the Pd–CO bonds are in the same range as those calculated for Cu­(I)–CO bonds in zeolites . As suggested by the X-ray structure of Pd complex [ 4 ]­(OTf) ( vide supra ), a weak attractive nonbonding CC···CO interaction was confirmed by the presence of the bond critical point between the corresponding C ipso and carbonyl carbon atoms, and its energy was estimated to be about 1.7 kcal mol –1 . While such interligand bonding is more common for carbonyl-containing transition metal NHC complexes exhibiting (pseudo)­octahedral, tetrahedral, and trigonal-bipyramidal geometry, the examination of CCDC base revealed only two examples of square-planar Rh­(I) complexes based on chelating bidentate NHC ligands, which display similar structural features as observed in the complex [ 4 ]­(OTf) .…”
Section: Resultssupporting
confidence: 75%
“…In the complex [ 4 ]­(OTf), the C–O bond distance of 1.117(4) Å is longer than in the bis­(NHC) complex [ 15 ]­(BF 4 ) (1.059(5) Å), indicating stronger π-backbonding from the Pd atom in agreement with the superior donor ability of phosphonium ylides compared to NHCs . Interestingly, the Pd–CO fragment in complex [ 4 ]­(OTf) was found to significantly deviate from the expected linear geometry (Pd1–C13–O1: 172.7(3)°) accompanied by a close proximity between the C ipso carbon atom of the mesityl group and the coordinating carbon atom (C13···C26: 3.055(4) Å) inferior to the sum of the van der Waals radii (3.4 Å), suggesting the occurrence of weak attractive π­(CC)···π*­(CO) interaction ( vide infra ) …”
Section: Resultsmentioning
confidence: 99%
“…In a more recent contribution, Lugan, César and Vayaev, described the preparation of a series of dimetallic complexes of Fe and Mn/Fe, from the stepwise metalation of IMes (IMes = 1,3-bis(2,4,6-trimethylphenyl)-2H-imidazol-2-ylidene), as it is shown in Scheme 10. 30 The characterization of the Mn/Li heterodimetallic complex 31 had been described by the same authors in a previous study. 31 The authors demonstrated that the electron-donating properties of both the normal and abnormal edges of the NHDC are increased by the metalation at the C4 and C2 positions.…”
Section: Scheme 7 Early Examples Of Anionic Ditopic N-heterocyclic Di...mentioning
confidence: 93%
“…The authors also tested the dimetallic Fe complex 34 in the hydrosilylation of ketones, where it proved to be more active than the related monometallic complexes of Fe bound to normal and abnormal (33) IMes. 30 Scheme 10. Stepwise formation of Mn/Fe and di-Fe NHDC-based complexes from IMes.…”
Section: Scheme 7 Early Examples Of Anionic Ditopic N-heterocyclic Di...mentioning
confidence: 99%
“…Taking into account the variation of ν CO frequencies (2–6 cm −1 ) theoretically predicted for different metal‐NHC rotamers of Mn(I) and Fe(II) complexes, [17a] we decided to perform a detailed conformational analysis of complex 5 by DFT calculations using G09/BP86‐D3/def2‐TZVP method. The geometry optimization revealed the existence of two minima on the potential energy surface corresponding to the conformers 5 a and 5 b (Figure 3) differing by the orientation of bicyclic NHC ligand.…”
Section: Resultsmentioning
confidence: 99%